The anthelmintic efficacy of natural plant cysteine proteinases against the equine tapeworm, Anoplocephala perfoliatain vitro. Issue 5 (7th September 2015) - Mansur, F.; Luoga, W.; Buttle, D.J.; Duce, I.R.; Lowe, A.E.; Behnke, J.M.
Abstract: Papaya latex has been demonstrated to be an efficacious anthelmintic against murine, porcine, ovine and canine nematode parasites, and even those infecting poultry, and it has some efficacy against rodent cestodes. The active ingredients of papaya latex are known to be cysteine proteinases (CPs). The experiments described in this paper indicate that CPs in papaya latex, and also those in pineapples, are highly efficacious against the equine cestode Anoplocephala perfoliata in vitro, by causing a significant reduction in motility leading to death of the worms. The susceptibility of A. perfoliata to damage by CPs was considerably greater than that of the rodent cestodes Hymenolepis diminuta and H. microstoma . Our results are the first to report anthelmintic efficacy of CPs against an economically important equine helminth. Moreover, they provide further evidence that the spectrum of activity of CPs is not restricted to nematodes and support the idea that these plant-derived enzymes can be developed into useful broad-spectrum anthelmintics.